ADAPTASI KEDIH (Presbitis thomasi Raffles, 1821) TERHADAP RUANG HORIZONTAL DAN VERTIKAL DI HUTAN SEKUNDER GUNUNG PAROY, ACEH BESAR. - Rosmalia, Rosmalia; Premana, Yasser; Ruskhanidar; Risnaldi, Kiki (Universitas Nusa Bangsa, 2025)
The Thomas langur (Presbytis thomasi) is a primate endemic to Aceh, threatened with extinction due to hunting and habitat destruction. They are found not only in conservation areas but also in other areas and secondary forests. Mount Paroy is one of the important Thomas langur habitats that has been damaged due to encroachment by local communities. In this area, Thomas langur are often hunted because they are considered pests by farmers. The conservation status of Thomas langur is listed as Vulnerable by the IUCN and Appendix II by CITES. This habitat change has resulted in changes in the food supply pattern of Thomas langur. Food trees are replaced by plantation crops. Therefore, Thomas langur must be able to adapt to food sources and sleeping trees of non-forest species. This study aimed to determine the feeding behavior and adaptation of Thomas langur in disturbed secondary forests using exploratory survey methods and data collection techniques using line transect. Recorded data included the horizontal coordinates of the Thomas langur ' feeding points and the height of the trees used for feeding and resting. Data were analyzed using the Maximum Convex Polygon (MCV) method. Results obtained in the Mount Paroy habitat showed horizontal movement of 29 ha, and vertical space was used at altitudes below 10 m. For food, Thomas langur on Mount Paroy consumes more leaves.